1993
DOI: 10.1002/1097-0142(19930601)71:11<3726::aid-cncr2820711141>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Role of brachytherapy in the management of the skull base meningioma treatment of skull base meningiomas

Abstract: Background. The treatment of primary and recurrent skull base meningiomas presents a formidable surgical problem. Methods. Fifteen patients with primary and recurrent skull base meningiomas were treated by means of interstitial irradiation with iodine 125 (125I) seed implantation. The physical characteristics of 125I enabled the authors to administer a minimum tumor dose ranging from 100 to 500 Gy at a low dose rate of 0.05–0.25 Gy per hour. Results. All 15 patients are alive at a median follow‐up of 29 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…11,15 Similarly, brachytherapy with iodine 125 seems to be of value for both recurrent and primary skull base meningiomas. 16…”
Section: Meningiomasmentioning
confidence: 99%
“…11,15 Similarly, brachytherapy with iodine 125 seems to be of value for both recurrent and primary skull base meningiomas. 16…”
Section: Meningiomasmentioning
confidence: 99%
“…The Nebraska group 9,17,26,27 seems to have the greatest experience with Iodine-125 seed implantation for the sole interstitial BT of skull base tumors. They predominantly treated, however, benign skull base tumors and malignant skull base primaries in the minority of their cases only.…”
Section: Experience With Seed Implant Btmentioning
confidence: 95%
“…Other therapies have been reported for these recalcitrant meningiomas 44 Castro et al 45 reported an 85% 5-year local control rate for a series of 223 tumors of the skull base treated with charged particle radiation. Kumar et al 46 described their use of brachytherapy for skull base tumors using 125 I seeds for their low dose rate. Mini-mum tumor doses of 100 to 500 Gy were delivered to the tumors and the seeds were placed directly in 2 of 15 patients and placed stereotactically in the remainder.…”
Section: Alternative Therapiesmentioning
confidence: 99%